Feasibility and acceptability of my electronic personal health record monitor (MY-EPHRM) - Umar Idris, Ibrahim; Lua, Pei Lin (2015)
Objectives: Smartphones could be used as a novel approach to improve medication adherence and patient’s behaviour; due to constant accessibility, and the provision of a repository for health and medication information. This study aimed to assess the feasibility and acceptability of the use of My Electronic Personal Health Record Monitor (My-ePHRM), a newly-developed application (software) for personal health record monitoring as well as the factors that predict its acceptability. Methods: A cross-sectional study using structured questionnaire was conducted on 363 potential users. Statistical analyses were performed using SPSS version 20.0. Description statistics and multiple logistic regression analysis were employed. Results: Majority of the participants were females (69.7%) with the mean age of 22 y (SD±1.7). Of the total number of the participants, 63.9% agreed that My-ePHRM was easy to operate and 50.7% thought that the language used was simple and easy to understand. Most of the participants found the features of My-ePHRM attractive (61.7%) and 52.1% would like to own it in the future. The majority agreed that My-ePHRM could increase health knowledge (57.0%), increase drug knowledge (54.0%) and could improve drug adherence (56.5%). Overall, (52.6%) believed that it was a good programme and (54.3%) would recommend it to others. Multiple logistic regression analysis revealed that ethnicity, gender and programme of the study participants did not predict My-ePHRM acceptance. Conclusion: My-ePHRM has been shown to be acceptable, simple and practical by its target users creating a huge potential in patients participation in documenting health-related activities.